An optimized genome-wide, virus-free CRISPR screen for mammalian cells - Xiong, Kai; la Cour Karottki, Karen Julie; Hefzi, Hooman; Li, Songyuan; Grav, Lise Marie; Li, Shangzhong; Spahn, Philipp; Lee, Jae Seong; Ventina, Ildze; Lee, Gyun Min; Lewis, Nathan E.; Kildegaard, Helene Faustrup; et al. (Cell Reports Methods, 2021)
Pooled CRISPR screens have been widely applied to mammalian and other organisms to elucidate the interplay between genes and phenotypes of interest. The most popular method for delivering the CRISPR components into mammalian cells is lentivirus based. However, because lentivirus is not always an option, virus-free protocols are starting to emerge. Here, we demonstrate an improved virus-free, genome-wide CRISPR screening platform for Chinese hamster ovary cells with 75,488 gRNAs targeting 15,028 genes. Each gRNA expression cassette in the library is precisely integrated into a genomic landing pad, resulting in a very high percentage of single gRNA insertions and minimal clonal variation. Using this platform, we perform a negative selection screen on cell proliferation that identifies 1,980 genes that affect proliferation and a positive selection screen on the toxic endoplasmic reticulum stress inducer, tunicamycin, that identifies 77 gene knockouts that improve survivability.
Keywords: Animals; CHO Cells; Clustered Regularly Interspaced Short Palindromic Repeats; Cricetinae; Cricetulus; CRISPR-Cas Systems; Genome; Lentivirus; Cas9; CHO; CRISPR; ER stress; genome wide; pooled screen; tunicamycin; virus free